2002
DOI: 10.1109/18.992777
|View full text |Cite
|
Sign up to set email alerts
|

On ensembles of low-density parity-check codes: asymptotic distance distributions

Abstract: We derive expressions for the average distance distributions in several ensembles of regular low-density parity-check codes (LDPC). Among these ensembles are the standard one defined by matrices having given column and row sums, ensembles defined by matrices with given column sums or given row sums, and an ensemble defined by bipartite graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 12 publications
(12 reference statements)
2
120
0
Order By: Relevance
“…Under the optimal maximum-likelihood (ML) decoding algorithm, both the finitelength analysis and the asymptotic analysis for LDPC codes and other ensembles of turbo-like codes become tractable and rely on the weight distribution of these ensembles (see e.g. [24], [25], and [26]). Various Gallager type bounds on ML decoders for different finite LDPC code ensembles have been established in [27].…”
mentioning
confidence: 99%
“…Under the optimal maximum-likelihood (ML) decoding algorithm, both the finitelength analysis and the asymptotic analysis for LDPC codes and other ensembles of turbo-like codes become tractable and rely on the weight distribution of these ensembles (see e.g. [24], [25], and [26]). Various Gallager type bounds on ML decoders for different finite LDPC code ensembles have been established in [27].…”
mentioning
confidence: 99%
“…Litsyn and Shevelev [68] showed that such an ensemble (referred to as "Ensemble A") has superior distance distribution compared to other ensembles they considered in [68], in the context of ML decoding.…”
Section: Remark 65mentioning
confidence: 99%
“…That is for every > 0 and any sufficiently large n, there exist an LDPC code of length n and rate 1 − h(p) − that has check degree (number of 1s in a row of the parity-check matrix) at most O(log 1 ), and probability of incorrect decoding at most 2 −E L (p, )n , for some E L (p, ) > 0. We refer the reader to [6], [8] for more details of this result. Suppose we call this codeĈ.…”
Section: A Existence Of Good Codesmentioning
confidence: 99%